Strategies for mastering synchronous translation art - Mahzuna Shavkatovna, Shoimqulova; Nilufar Soliyevna, Nosirova; Munavvar Ahmadovna, Soliyeva; Shahlo Shaydulloevna, Kaxxarova (International Journal of Psychosocial Rehabilitation, 2020)
Not only is it a synchronous translation process, but the translation itself is also a very complex process. Translators use a variety of methods and strategies to succeed. We tried to express all strategies of mastering synchronous translation in this article.